GENERAL ISSUES OF IRON METABOLISM AND PATHOGENESIS OF IRON DEFICIENCY ANEMIA - T. E. Potemina; C. A. Volkova; S. V. Kuznetsova; A. V. Pereshein (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Iron is an essential trace element, because it is required for adequate erythropoietic function, oxidative metabolism, and cellular immune responses. In this article, we analyze the mechanisms of iron homeostasis and pathogenesis of iron-deficiency conditions and iron-deficiency anemia.